УКРАЇНСЬКА ДІАСПОРА В РОСІЙСЬКІЙ ФЕДЕРАЦІЇ: СТАН ТА ПЕРСПЕКТИВИ (Zaporizhzhia Historical Review, 2021)
The article is devoted to a problem of the Ukrainian Diasporas in Russia and to the series of scientific and practical questions connected with this problem. Historical conditions, ways of formation of considerable number of the Ukrainian population and peculiarities of their settling in Russia are investigated. The basic categories of ethnic Ukrainians which form Diasporas in Russia are formulated. The separate attention is paid to the modern state of the Ukrainian Diasporas, their social, political and cultural role in the life of Russia, degree of preservation of their ethnic identity, and to cultural requirements of Diasporas. The article illustrates the activity of the Ukrainian Government directed to the provision of the requirements of Diasporas and strengthening of relations with it.